TINJAUAN YURIDIS TERHADAP DOKTER DENGAN PASIEN KECANTIKAN KULIT TANPA MENGGUNAKAN INFORMED CONSENT - Agusto, Yosafat; Thomas Abbon; Nanin Koeswidi Astuti (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
The importance of informed consent to the patient should be used for medical purposes to be aware of the presence of other diseases or not before any medical action is chosen. The formula of the problem in this study is how do the regulations governing the actions of doctors in patient care and how are the treatment actions that do not use informed consent. The research method used is normative juridical, using secondary data in the form of legal materials consisting of primary, secondary and tertiary legal materials.Based on the resultsxof the study and the author's analysis that medical actions taken by doctors toxpatients should be guided by informed consent. Because in law No. 29 of 2004 on The Practice of Medicine, Decree No. 290 / Menkes / Per / III / 2008 Concerning The Approval of Medical Action, Decree No. 1419 / Men.Kes / Per / X / 2005 on the Implementation of Medical Practice, Law No. 36 of 2009 on Health is clearly said that any Medical Or Dentistry Action to be performed by a doctor or dentist against the patient must be approved.